Study guides

☆☆

Q: What is 7n?

Write your answer...

Submit

Still have questions?

Related questions

7n(n−1)

7n = 91n = 91÷7n = 13

7n-6 = 1

n7-12

11

7n = 28n = 28/7 = 4

-7n2 + 74n + 33 = -7n2 + 77n - 3n + 33 = -7n*(n - 11) - 3*(n - 11) = =(-7n - 3)*(n - 11) = -(7n +3)*(n - 11)

2-n-7n = 2-8n

9n-2=7n+50 7n+9n=50+2 16n=52 n= 3.25

2 - 7n = 6therefore 7n = 2 - 6 = -4 and so n = -4/7 Then 5m + 7n = 6.4 becomes 5m - 4 = 6.4 so that 5m = 10.4 and then m = 10.4/5 = 2.08

This question as written can be taken two ways: 9m + 6n - 3m + 7n = 6m + 13n, or (9m + 6n) - (3m + 7n) = 9m + 6n - 3m - 7n = 6m - n

63

(64m-3n)*7n*3m = 1344m2n - 63mn2

(10, 2)

The expression could be: 2 -7n

7n + 1 = 6n + 8 7n=6n+7 (minus 1 from each side) n=7 (7n-6n equals n, you are left with n=7)

It is 336n.

Gather like terms. The - 2 and 4; the 7n and 3n. 7n - 2 + 3n + 4 = 10n + 2

7n = 7 divide by 7 on both sides n = 7

7n - 2 + 3n + 4 = 7n + 3n - 2 + 4 = 10n + 2 which can be simplified to 2(5n +1)

-7n - 8 + 6 = 13 - 2 Add 2 to each side: -7n - 8 + 6 + 2 = 13 simplify: -7n = 13 n = -13/7 = -16/7

7n-36=34 Add 36 to both sides: 7n=70 divide both sides by 7: n=10

in an equation it would be 7n>42 (divide both sides by 7) = n>6

n2 + 7n - 44 (n + 11)(n - 4)

6m + 5n - 4m + 7n = 2m + 12n